Actinomyces‐infected bronchopulmonary sequestration: An uncommon pathogen in a rare anomaly - Aasir M. Suliman (14150217) (2024)
Key Clinical Message Bronchopulmonary sequestration, a rare congenital anomaly, involves a nonfunctioning lung tissue mass supplied by anomalous vessels. It is rarely infected by Actinomyces, further complicating the clinical presentation, with limited reported cases. This case highlights the distinctive clinical aspects, diagnostic challenges, and successful management strategies of such a rare clinical entity. Other Information Published in: Clinical Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/ccr3.8984